2022
DOI: 10.1002/cpt.2563
|View full text |Cite
|
Sign up to set email alerts
|

PharmVar GeneFocus: CYP3A5

Abstract: The Pharmacogene Variation Consortium (PharmVar) catalogs star (*) allele nomenclature for the polymorphic human CYP3A5 gene. Genetic variation within the CYP3A5 gene locus impacts the metabolism of several clinically important drugs, including the immunosuppressants tacrolimus, sirolimus, cyclosporine, and the benzodiazepine midazolam. Variable CYP3A5 activity is of clinical importance regarding tacrolimus metabolism. This GeneFocus provides a CYP3A5 gene summary with a focus on aspects regarding standardized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 76 publications
0
26
0
1
Order By: Relevance
“…GCs ( 28 ) and tacrolimus ( 29 ) are the most frequently used pharmacological agents for our cohort, which are both metabolized by CYP3A5 enzyme. The A to G substitution at rs776746 polymorphism is responsible for aberrantly spliced transcript and low protein expression of CYP3A5 in many populations ( 30 ). Consistent with the previous study ( 29 ), our results demonstrated an association between the dominant model of CYP3A5 rs776746 polymorphism and poor response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…GCs ( 28 ) and tacrolimus ( 29 ) are the most frequently used pharmacological agents for our cohort, which are both metabolized by CYP3A5 enzyme. The A to G substitution at rs776746 polymorphism is responsible for aberrantly spliced transcript and low protein expression of CYP3A5 in many populations ( 30 ). Consistent with the previous study ( 29 ), our results demonstrated an association between the dominant model of CYP3A5 rs776746 polymorphism and poor response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There are 34 defined *-haplotypes for the CYP3A4 and five in the CYP3A5 gene designated by PharmVar ( https://www.pharmvar.org/ ). Recently, three CYP3A5 alleles ( CYP3A5*2, *4, and *5 ) have been reclassified as part of the CYP3A5*3 suballeles ( Rodriguez-Antona et al, 2022 ). Among those haplotypes, the most widely studied genetic variant is the CYP3A5*3 allele (rs776746), characterized by a splice defect in intron 3.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these two well-recognized haplotypes, there are 37 additional *-allele haplotypes defined for CYP3A4 and CYP3A5 . A recently published review presented a comprehensive summarization of all CYP3A5 *-alleles ( Rodriguez-Antona et al, 2022 ). Here we give an overview of all CYP3A4 *-alleles.…”
Section: Introductionmentioning
confidence: 99%
“…CYP3A5 enzymes are involved in the metabolism of a variety of clinical drugs such as tacrolimus, cyclosporin, saquinavir, midazolam, vincristine, and statins (Rodriguez-Antona et al, 2022). The strongest evidence of the clinical effects of genetic variation in CYP3A5 is for the metabolism of tacrolimus, where the guidelines recommends the standard dosing of medication based on the tacrolimus package insert for transplant recipients with the poor metabolizer phenotype (CYP3A5 *3/*3), and an increased dose of tacrolimus for individuals with an extensive (CYP3A5 *1/*1)…”
Section: Discussionmentioning
confidence: 99%
“…or intermediate metabolizer phenotype (CYP3A5 *1/*3) to achieve therapeutic drug concentrations (Birdwell et al, 2015). The CYP3A5*3 allele frequency is highest in Europeans (92%), Asians (67-75%), and Near-Eastern populations (84%), and lowest in African American/Afro-Caribbeans (32%) and Sub-Saharan Africans (24%) (PharmGKB, 2021f) (Rodriguez-Antona et al, 2022). For Latinos, the frequency reported was 77% (on average), which is identical to the frequency detected in our cohort.…”
Section: Discussionmentioning
confidence: 99%